(untitled) (Global Journal of Computer Science and Technology, 2025)
Modern cloud-native applications require new-age architectural paradigms that can provide instantaneous responsiveness in handling heterogeneous data streams over distributed computing environments Event-driven microservices architectures come into play as groundbreaking solutions to counter the inherent constraints of monolithic systems and traditional batch-based processing pipelines The architectural system brings together containerized microservices and advanced event streaming infrastructure to support asynchronous communication patterns that do away with legacy blocking operations Machine learning algorithms enable smart event prioritization and predictive resource allocation dynamically adjusting to changing workloads with adaptive scaling options Multi-cloud deployment strategies guarantee outstanding fault tolerance with full self-healing options and geographical redundancy deployments Performance optimization approaches involve connection pooling in-memory caching and streaming computation models that cut end-to-end processing latency by a significant margin Horizontal scaling support allows dynamic capacity options with constant latency characteristics despite changing operational loads Applications within the real world cover industrial automation medical monitoring smart town infrastructure financial services autonomous transportation and supply chain management displaying tremendous upgrades in machine responsiveness useful resource usage performance and operational reliability over traditional architectural styles